Analysis of Spatial Planning in Landslide Hazard Zones in Banyumas Regency, Indonesia - Suwarno Suwarno; Erny Rachmawati; Mohd Hairy Ibrahim; Sutomo Sutomo; Aris Slamet Widodo; Sakir Sakir; Hercules Pungky Naga Dewa (Forum Geografi)
Banyumas Regency is an area that with a high potential for landslide hazards. These pose a serious threat to spatial planning. This research aims to analyse land use in landslide-prone areas; to compare spatial planning strategies in the region; and to offer recommendations for effective spatial planning to reduce landslide risks. The application of a physical approach, incorporating ten parameters to assess landslide hazard levels, can be considered to be optimal. The research findings have significant implications for spatial planning and disaster risk management in Banyumas Regency. The analysis results indicate that certain community activity areas, such as residential, tourism and industrial zones, are located in areas with low to moderate landslide hazards. This demonstrates that the regency prioritises disaster risk considerations in land utilisation planning. The research has several limitations, including the lack of data validation and historical landslide data in Banyumas Regency concerning landslide hazard assessment. In addition, the study only focuses on landslide hazard areas in the central community activity zone, but does not include residential areas in other designated zones.